Why it is good to communicate the bad: understanding the influence of message framing in persuasive communication on consumer decision-making processes - Gier, Nadine R.; Krampe, Caspar; Kenning, Peter (Frontiers in Human Neuroscience, 2023)
One approach to bridge the gap between consumer intentions and behavior is persuasive communication to reinforce their intentions and thereby support their behavior change. Message framing has proven to be a useful persuasive communication tool. However, message framing is considered more complicated than other types of framing because, in addition to concept-specific elements, it is also strongly influenced by and in turn influences emotions. Therefore, it is impossible for consumers to verbally express their true attitudes, so the challenge is to explain and measure its impact. The aim of this research is to help in this regard by suggesting a theoretical model to understand how message framing is processed from a consumer neuroscience perspective. More precisely, the factors that constitute message framing are systematized and building on reflectiveimpulsive model and a neural emotion-cognition framework interpreted to explain the persuasive effects of message framing. A functional magnetic resonance imaging (fMRI) experiment is used to examine the effects of message framing for four different frame types that are hypothesized to affect consumer information processing differently. The results suggest that communication strategies should take into account the valence of the objects and the frame used. The behavioral results partially confirm the assumption that two types of information processing could take place as suggested the reflective-impulsive model. At the neural level, using the network perspective, the results show that certain brain regions primarily associated with emotional and cognitive interaction processes are active during processing, depending on the framing of the message. In cases of indirect avoidance value-consistent framing, it may be good to communicate the bad in the appropriate frame to influence information processing.